FROM ENTREPRENEURIAL INTENTION TO ACTION: CROSS-COUNTRIES EMPIRICAL EVIDENCES - Tiago, Flávio Gomes Borges; Faria, Sandra Micaela Costa Dias; Couto, João Pedro de Almeida; Tiago, Maria Teresa Pinheiro Melo Borges (European Scientific Journal, ESJ, 2014)
As research on entrepreneurship matured, the activators and inhibitors of entrepreneurial intention has been widespread. However, the implementation of ideas and development of new innovative enterprises is more than intent. It requires action. Therefore, to clarify what is known about the intention of entrepreneurship and shed light on important issues that could help entrepreneurs and policy makers to develop a more comprehensive understanding of why some countries tend to be more entrepreneurial than others, the intent of this study is to use existing theories and change the ratio of the fundamental variables. The main variables were compared directly using a probit model applied to a sample of 10,267 entrepreneurs from twenty-seven countries. The results of the study offer a different perspective from previous research in our understanding of entrepreneurship beyond the entrepreneurial intention and therefore, provides insight into the decision in creating new.